The skills of helping individuals, families, groups, and communities - Shulman, Lawrence (Cengage learning empowerment series, 2016)
This book introduces a model for the helping process based on an 'interactional' approach, which uses a variety of theories and skills to build on the client-helper relationship. By presenting the core processes and skills in the chapters on work with individuals, the author shows how common elements exist across stages of helping and across different populations. These processes and skills reappear in the discussions of group, family, and community work